DETERMINANTS OF CUSTOMER TRUST IN FINTECH AS A MEANS OF PAYMENT THROUGH AN APPROACH TECHNOLOGY ACCEPTANCE MODEL - Adele Mailangkay; Edhi Juwono (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to determine and analyze the determinants of customer trust in Fintech as a means of payment through the Technolgy Acceptance Model approach. The research method uses quantitative deccipitive, with a total sample of 150 respondents based on the opinion of Hair et al. (2019).  The results showed   that perceived ease of use has a positive and significant effect on perceived usefulness.  Perceived ease of use and perceived of usefulness have a positive and significant effect   on attitude. Perceived of usefulness and attitude has a positive and significant effect on the intention to use Fintech